2005
DOI: 10.1016/j.ccell.2005.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Sibling Presence in Pediatric ICU

Abstract: Critical illness of a child affects all members of the family, including well brothers and sisters. Stress in their lives results from changes in parental behaviors, caregiving arrangements, and family relationships. These changes, along with limited understanding and information about the crisis, create feelings of confusion, loneliness, jealousy, and sadness, as well as physical symptoms and behavior changes. Educating pediatric ICU nurses about the needs and reactions of well siblings enables them to optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
0
19
0
8
Order By: Relevance
“…To minimize conflicts generated in the PICU's context, authors (5,(15)(16)(17) emphasize the benefits of communication between the team and family, in addition to the participation of the family in decision-making concerning care. The process of professional partnership involving an open and supportive, non-directive dialog between nurses and patients helps to reduce negative interactions.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize conflicts generated in the PICU's context, authors (5,(15)(16)(17) emphasize the benefits of communication between the team and family, in addition to the participation of the family in decision-making concerning care. The process of professional partnership involving an open and supportive, non-directive dialog between nurses and patients helps to reduce negative interactions.…”
Section: Discussionmentioning
confidence: 99%
“…To honor siblings' presence and unique contributions, nurses may explore with parents how to include siblings in meaningful ways. 16,19,27,48,62 An important aspect is obtaining parental permission and respecting parental preferences about end-of-life communication while providing the siblings with honest, accurate information. 8,10,60,62 Dialogue with siblings should be congruent with the siblings' age and developmental level, and not euphemistic or metaphoric.…”
Section: Explanationmentioning
confidence: 99%
“…16,19,27,48,62 An important aspect is obtaining parental permission and respecting parental preferences about end-of-life communication while providing the siblings with honest, accurate information. 8,10,60,62 Dialogue with siblings should be congruent with the siblings' age and developmental level, and not euphemistic or metaphoric. 42,48,59,60 Supporting the Family After the Child's Death Nurses may feel awkward and unsure about to how to support a family once a child has died.…”
Section: Explanationmentioning
confidence: 99%
“…(3,6,7,11) On the other hand, other studies conducted by nurses show that explaining to the child what he/she is about to see and experience would prevent eventual traumas. (3,7,8,11,12) Several studies (2,3,5,11) have shown that a child's visit to a relative in ICU is fundamental, as the child's anxiety, abandonment and fear of death feelings are found reduced after the visit; in addition, having a notion of the disease, the child becomes participant in the hospitalization process. (7,8) Nicholson et al (2,3) studied a sample of 20 children, divided in two groups.…”
Section: Review On Children Visiting Intensive Care Unitmentioning
confidence: 99%
“…(8) Additionally, children psychology scholars emphasize the child's cognitive, intellectual, affective and emotional abilities, demystifying the idea that children are not capable to deal with pain and suffering. By visiting a critically ill patient, the child takes part in the family reality, and will be able to understand the family routine and behavior changes.…”
Section: Introductionmentioning
confidence: 99%